Paediatric heart care in India. Issue 8 (14th July 2008) - Kumar, R K; Shrivastava, S
Abstract : There have been few systematic efforts to define the burden of paediatric heart disease in India. Estimates based on published studies on congenital heart disease (CHD) at birth suggest a massive CHD burden. Absolute numbers of children with other heart diseases are also likely to be substantial. Given the enormity of the problem the number of paediatric heart programmes and specially trained paediatric cardiologists and paediatric cardiac surgeons are woefully inadequate. They are largely clustered in those parts of India that are experiencing improving economy and human development. For the average family the cost of care of a child with heart disease is prohibitive because care of children with heart disease often requires considerable human and material resources, together with sophisticated technology. While paediatric cardiology is only now being recognised in India as a major specialty, there is a need to intensify efforts to develop the specialty especially in those parts of India where there are very few centres. The present challenges are many and they include obtaining representative data on disease burden, establishing quality institutions with comprehensive paediatric cardiac programme training a cadre of professionals for paediatric heart care, developing cost-effective management strategies and improving awareness on diagnosis and management of paediatric heart diseases.